2015
DOI: 10.1016/j.optmat.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Direct band gap In Ga1−As/Ge type II strained quantum wells for short-wave infrared p–i–n photodetector

Abstract: a b s t r a c tWe theoretically investigate GaAs/Ge/InGaAs as a quantum wells for the design of short-wave infrared p-i-n photodetectors in which the quantum well Ge/InGaAs is the active region. At room temperature, strained Ge/In x Ga 1Àx As becomes a direct band gap when In composition x is lower than 2.5% and 5% respectively. We have calculated the electronic band parameters for the heterointerface Ge/In x Ga 1Àx As. Then, a type-II strain GaAs/Ge/In 0.35 Ga 0.65 As/GaAs quantum wells heterostructure optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…We previously reported growth studies which confirm the incorporation of Bi and P in the wells and barriers respectively [23]. The purpose of the present work is to exhibit the effects instigated by the bismide states, taking into account the influence of the modified band offset parameters (Table 1) [24,25] on band structures and optical gain spectra for a strained GaAsP/GaAsBi/GaAsP QWs. This latter effect is supported by the fact that the modified offset parameters [26] play a fundamental role in energy dispersion, and thus in optical gain.…”
Section: Quantum Well Design Studiesmentioning
confidence: 81%
See 1 more Smart Citation
“…We previously reported growth studies which confirm the incorporation of Bi and P in the wells and barriers respectively [23]. The purpose of the present work is to exhibit the effects instigated by the bismide states, taking into account the influence of the modified band offset parameters (Table 1) [24,25] on band structures and optical gain spectra for a strained GaAsP/GaAsBi/GaAsP QWs. This latter effect is supported by the fact that the modified offset parameters [26] play a fundamental role in energy dispersion, and thus in optical gain.…”
Section: Quantum Well Design Studiesmentioning
confidence: 81%
“…Moreover, it was computed using the refractive indices n op extracted from Table 1, following the procedure assumed in Ref. [24]. The carried out calcu-lations at 300K indicated that the incorporation of bismide reduces the radiative efficiency of the structure (Figure 8a).…”
Section: Optical Gain and Radiative Current Calculationmentioning
confidence: 99%
“…Compared with the other types of PDs, infrared PDs have great importance in numerous civilian and military applications, including heat capacity mapping, thermal remote sensing, target tracking and environment monitoring . Common materials for infrared PDs include GaSb, GaAs, InAs, and HgCdTe . Recent years, 1D nanostructures are also used in infrared PDs.…”
Section: D Inorganic‐nanostructures‐based Flexible Pdsmentioning
confidence: 99%